Analisis Postur dan Perbaikan Metode Kerja dengan Metode Rapid Upper Limb Assessment (RULA) pada Industri Minyak Goreng - Muhammad Rizky Ramadhani; Andarmadi Jati Abdhi Wasesa (CV. ALIM'SPUBLISHING, 2026)
The manual loading of finished goods in the cooking oil industry has the potential to cause unergonomic work postures and musculoskeletal disorders (MSDs). This study aims to analyze the work posture of loading workers at CV. OASE using the Rapid Upper Limb Assessment (RULA) method, identify body complaints through the Nordic Body Map (NBM), and provide suggestions for ergonomic work improvements. Data were collected through observation, interviews, posture documentation, NBM questionnaires for 12 workers, and posture angle measurements using the Angle Meter 360 application for 4 workers. The results showed that all workers obtained a final RULA score of 7, including high risk and requiring immediate improvement. The NBM results showed dominant complaints in the waist with a score of 44 and the lower neck with a score of 42, including very high risk. The contributing factors were a bent posture of more than 60°, a carton load of more than 10 kg, and repeated lifting. Suggested improvements include the use of an adjustable conveyor belt so that the carton position is parallel to the worker's waist. The RULA simulation showed a score decrease from 7 to 6, so the risk changed from high to medium. These improvements are expected to reduce MSD complaints and increase the comfort and productivity of loading workers.